Preferences for Employment Protection and the Insider-Outsider Divide - Elvire Guillaud; Paul Marx (Institute for the Study of Labor (IZA), 2013)
Insider-outsider theory suggests that in dual labour markets two groups have opposing preferences regarding protection against dismissals: insiders defend employment protection, because it increases their rents. Outsiders see it as a mobility barrier and demand deregulation. Similar divides are expected for unemployment benefits: as insiders and outsiders have diverging unemployment risks, they should demand different levels of protection. Although these views are influential in the political economy debate, there is little empirical research on the effect of contract types on social and labour market policy preferences. We use a novel data set collected in the most recent presidential contest in France, which combines detailed information on respondents' employment status with questions measuring attitudes towards dismissal regulation and other labour market policies. Going beyond insider-outsider theory, we argue and show empirically that the effect of membership in either segment is moderated by the employment situation in workers' occupation.
Keywords: J08; J41; K31; 330; employment protection; insider-outsider theory; political preferences; France; single employment contract